PENGARUH KUALITAS LAYANAN,CITRA PERUSAHAAN DAN NILAI NASABAH TERHADAP KEPUASAN DAN DAMPAKNYA PADA LOYALITAS NASABAH (Studi Pada Nasabah Tabungan PT. Bank Negara Indonesia Kantor Kas Karang Turi Semarang)THETIC CENTER SEMARANG) - Sofiana Adhi Putri, 14.05.51.0198; Maskur, Ali (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the effect of service quality, corporate image, and customer value on satisfaction and its impact on loyalty. The population in this study are all depositors who deposit funds in the form of demand deposits, savings and time deposits in Bank BNI KarangTuri Semarang Cash Office. Sampling technique in this research use purposive sampling, because in determining sample based on certain criterion, that is: active customer at least 3 times in 1 year that transact and save fund in the form of demand deposit, saving and deposit at Bank BNI KarangTuri Cash Office Semarang . The analysis tool used is multiple linear regression analysis using SPSS 20. The result of the fit model test shows that the three variables have influence to customer satisfaction and loyalty together, while the partial test shows that there is influence of service quality to satisfaction and loyalty, the influence of corporate image to customer satisfaction and loyalty, the influence of customer value to satisfaction and customer loyalty and the effect of customer satisfaction on customer loyalty. Keywords: Service Quality, corporate image, customer value, customer satisfaction and loyalty.